Arthur Green : Hasidism for tomorrow - Green, Arthur, 1941- (Library of contemporary Jewish philosophers ;, 2015)
Arthur Green is Rector of the post-denominational Rabbinical School and Irving Brudnick Professor of Jewish Philosophy and Religion at Hebrew College in Newton, Massachusetts. Originally ordained as a Conservative rabbi, Green considers himself a neo-Hasidic Jew, identifying with none of the established Jewish denominations. He combines historical knowledge of the Jewish mystical tradition with an original constructive theology. Recognized as both a rabbi and a scholar, Green has sought to make spiritual pursuit an essential part of committed Jewish life. Through scholarship, educational work, and popular teaching, he has contributed to the growth and vitality of Judaism in America and helped promote neo-Hasidism as Jewish spirituality for the 21st century.